Gastroprotective effect of topiramate on indomethacin‐induced peptic ulcer in rats: Biochemical and histological analyses. Issue 5 (18th March 2022) - Jafari, Abbas; Andishfar, Nafiseh; Esmaeilzadeh, Zeinab; Khezri, Mohammad Rafi; Ghasemnejad‐Berenji, Morteza
Abstract: Topiramate is an anticonvulsant drug effective against a wide range of seizures and epilepsies. The present study was conducted to investigate the possible protective effect of topiramate on indomethacin‐induced gastric mucosal damage in rats. The animals were randomly distributed into four experimental groups with 10 animals in each group. Group 1 was the control group received vehicle only (DMSO at 1:4 (w/v)), group 2 was the model group received indomethacin (50 mg/kg; i.p.), and groups 3 and 4 received topiramate (100 mg/kg; i.p.) and ranitidine (100 mg/kg; i.p.), respectively, 1 h before indomethacin (50 mg/kg; i.p.). The efficacy of topiramate was compared with ranitidine. Animals were euthanized 4 h after indomethacin administration, and gastric tissues were collected for macroscopical, histopathological, and biochemical analyses. The mucosal lesions in the gastric corpus were evaluated by pathological examinations. The results revealed that the administration of indomethacin caused evident gastric mucosal damage with morphological and histological manifestation, whereas topiramate pretreatment extensively ameliorated the gastric injuries. Topiramate pretreatment also reduced the contents of tissue malonaldehyde, enhanced ferric reducing antioxidant power value and glutathione levels, and increased the activity of superoxide dismutase, catalase, and glutathione peroxidase in gastric mucosa compared to the model group. Our results indicate that topiramate might possess a protective role against indomethacin‐induced gastric ulcers by inhibition of oxidative stress in gastric tissue.